Reduced responsiveness of blood leukocytes to lipopolysaccharide does not predict nosocomial infections in critically ill patients - Van Vught, LA; Wiewel, MA; Hoogendijk, AJ; Scicluna, BP; Belkasim, H; Horn, J; Schultz, MJ; Van der Poll, T (Critical care (London, England), 2015)
Compared with healthy subjects, whole blood leukocytes of patients were less responsive to ex vivo stimulation with LPS, as reflected by strongly reduced TNF?, IL-1? and IL-6 levels in culture supernatants. Conclusion The extent of reduced LPS responsiveness of blood leukocytes in critically ill patients on the first day after ICU admission does not relate to the subsequent development of ICU-acquired infections.